ENCULTURATION AS A BASIS FOR ORGANIZING THE EDUCATIONAL ENVIRONMENT AT SCHOOL (American Journal of Research in Humanities and Social Sciences, 2024)
This article discusses the question of what role education plays in the process of inculturation of the individual, with the help of what universal mechanisms this is carried out. It is concluded that nowadays in educational institutions it is necessary to talk not only about improving the process of socialization, which can form not only educated people, but also about creating a full-fledged inculturation process aimed at forming cultured people.